О терминологических аспектах языковой политики - Гринев-Гриневич, С.В. (Термінологічний вісник, 2011)
Рассматриваются терминологические аспекты формирующейся области знания, которую предлагается назвать лингвополитологией. Делается попытка представления структуры новой науки и содержания ее основных разделов. Отмечается, что, несмотря на очевидную необходимость учета терминологических аспектов языковой политики, в настоящее время нет оснований говорить о сознательном плановом подходе к вопросам развития языков. Однако в терминологии сформулирован ряд принципов содействия развитию языка. Terminological aspects of a newly formed scientific discipline that is suggested to be named linguopolitology are analysed. The structure and the content of the new discipline are presented. It is stated that though there is an evident need in paying attention to terminological aspects of language policy and planning, at present there is lack of planning in questions of language development. However in terminology science a number of principles of enhancing development of special vocabulary are developed though there is small chance that they would be used in determining state language policy.